The effect of 12 weeks of basic soccer training on violence tendency, psychological resilience, social anxiety in 12-14 years old children - Ozcan, Busra; Celikel, Baha Engin; Erdogan, Ramazan; Karadag, Mustafa; Aydogdu, Volkan; Ugurlu, Fatih Mehmet; Orhan, Serdar (Frontiers Media Sa, 2025)
Background: Regular exercise during childhood impacts not only physical development but also emotional stability, social adaptation, and behavioral control. Therefore, the present study aimed to examine the effects of a 12-week introductory football training programme on violent tendencies, psychological resilience, and social appearance anxiety in children aged 12-14. Methods: A randomized controlled design was used, with 40 children assigned to an experimental group (n = 20) or a control group (n = 20). The experimental group completed 60-min football sessions three times a week, while the control group did not participate in structured activity. The program included a 20-min warm-up, technical and tactical exercises, game-based activities, and a cool-down, targeting physical, technical, tactical, and psychosocial development. Data were collected using the VTS, PRS, and SAAS scales.Statistical analyses were performed using SPSS version 25 (IBM Corp., Armonk, NY, USA), with mixed-design ANOVA, significance set at p < 0.05, and effect sizes reported as partial eta-squared (eta p(2)). Results: No significant difference was observed in violence tendency scores in the experimental group (p = 0.939). However, a decrease was observed in psychological resilience scores in comparison to pre-test values, and this decrease approached the threshold of significance with a medium effect size (p = 0.153, eta p(2) = 0.053). This finding suggests that the intervention may have a limited effect on psychological resilience. While no significant change was detected in the social appearance anxiety variable in the experimental group (p = 0.120), a significant decrease in anxiety levels was observed in the control group (p = 0.029). This finding suggests that factors other than the experimental intervention may have been effective in the control group. Conclusions: In conclusion, the 12-week football training programme demonstrated no significant short-term effect on violent tendencies or social appearance concerns, but may have a temporary effect on psychological resilience. The findings indicate that the impact of sports participation on psychosocial development in children is multifaceted and contingent on individual differences.
Keywords: violence tendency; psychological resilience; social anxiety; footbal; sports psychology